Design of miniaturised UWB antenna for oil pipeline imaging. Issue 21 (1st October 2015) - Kumar, T.; Gautam, A.K.; Kanaujia, B.K.; Rambabu, K.
Abstract : A novel design of miniaturised ultra‐wideband (UWB) antenna for oil pipeline imaging is presented. The proposed prototype uses a simple eye‐shaped slot radiator and two ground planes at the same side of the dielectric substrate. The proposed antenna design exhibits an enhanced bandwidth of 20.3 GHz from 3.2 to 23.5 GHz (for return loss <10 dB) which provides a wide usable fractional bandwidth of more than 152% with ultra‐compact area of 14 mm × 12 mm. The simulated and measured results confirm the benefits of the proposed design and reduction in the antenna size with enhanced UWB performance.